Hypothetical Learning Trajectory Materi Sistem Persamaan Linear Tiga Variabel: Konteks Jajanan Khas Kepulauan Riau - Husna, Asmaul; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Susanti, Ely; Nusantara, Duano Sapta (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
This study aims to design a learning trajectory for the Three-Variable Linear Equation System (SPLTV) by applying Indonesian Realistic Mathematics Education (PMRI) with the context of typical Riau Islands snacks. The research methodology involved three stages, namely preparing for the experiment, design experiment, and retrospective analysis. Data were collected through documentation and interviews, then analyzed by data reduction, data presentation, and conclusion drawing. The research subjects were 15 3rd semester students of the Mathematics Education Study Program at Riau Islands University. The results of the research are in the form of a hypothetical learning trajectory design in learning SPLTV with the context of typical snacks of the Riau Islands. The learning trajectory begins by linking students' learning experiences with the concepts to be presented. During learning, students apply the SPLTV concept to contextual problems. In the end, they are able to apply the SPLTV concept in different contexts, demonstrating an understanding of the material. This contextualized learning experience plays an important role in improving students' understanding of SPLTV.